Long-term priming of hypothalamic microglia is associated with energy balance disturbances under diet-induced obesity - Fernández-Arjona, María del Mar; León-Rodríguez, Ana; Mateos-Grondona, Jesús; López-Ávalos, María Dolores (Wiley, 2022)
Exposure of microglia to an inflammatory environment may lead to their priming and exacerbated response to future inflammatory stimuli. Here we aimed to explore hypothalamic microglia priming and its consequences on energy balance regulation. A model of intracerebroventricular administration of neuraminidase (NA, which is present in various pathogens such as influenza virus) was used to induce acute neuroinflammation. Evidences of primed microglia were observed 3 months after NA injection, namely (1) a heightened response of microglia located in the hypothalamic arcuate nucleus after an in vivo inflammatory challenge (high fat diet [HFD] feeding for 10 days), and (2) an enhanced response of microglia isolated from NA-treated mice and challenged in vitro to LPS. On the other hand, the consequences of a previous NA-induced neuroinflammation were further evaluated in an alternative inflammatory and hypercaloric scenario, such as the obesity generated by continued HDF feeding. Compared with sham-injected mice, NA-treated mice showed increased food intake and, surprisingly, reduced body weight. Besides, NA-treated mice had enhanced microgliosis (evidenced by increased number and reactive morphology of microglia) and a reduced population of POMC neurons in the basal hypothalamus. Thus, a single acute neuroinflammatory event may elicit a sustained state of priming in microglial cells, and in particular those located in the hypothalamus, with consequences in hypothalamic cytoarchitecture and its regulatory function upon nutritional challenges.
Keywords: Hipotálamo; Shigh fat diet; Hypothalamus; MHCII; Microglia priming; Neuroinflammation; Obesity; Neuraminidase